2018
DOI: 10.1016/j.anpedi.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la sensibilización a Der p 1 y Der p 2 en una población pediátrica del Norte de Portugal

Abstract: Der p 1 and Der p 2 are dominant allergens in our population and there may be benefits in determining these molecular allergen levels in patients with a positive prick-test and a clinical indication for sIT prior to a decision of initiating sIT or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
3
2
Order By: Relevance
“…Our results show that the levels of IgEDerp2 is higher than IgEDerp1 3 , 6 , 7 , 19 , 20 without reaching statistical significance. However, since the sIgE production describes a non-linear curve and the commonly used method is an ELISA whose curve is not linear either, we can only say that there is a higher sIgE production for HDM group 2.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Our results show that the levels of IgEDerp2 is higher than IgEDerp1 3 , 6 , 7 , 19 , 20 without reaching statistical significance. However, since the sIgE production describes a non-linear curve and the commonly used method is an ELISA whose curve is not linear either, we can only say that there is a higher sIgE production for HDM group 2.…”
Section: Discussioncontrasting
confidence: 67%
“…While other studies showed a lower IgE responses to Der p 1 and Der p 2 for Australia (74–77%) and Singapore (63%) 18 . Our series shows the presence of the 4 phenotypes in production for IgEDerp1 and IgEDerp2 3 , 6 , 7 , 19 , 20 . The majority group DP (IgEDerp1 and IgEDerp2 double positives), significantly higher, followed by DN (double negative to IgEDerp1 and IgEDerp2) being the second most relevant group.…”
Section: Discussionmentioning
confidence: 67%
“…Unless for immunotherapy clinical trials, this double negative group Derp1 and Derp2, should be excluded. Our results show that the levels of IgEDerp2 is higher than IgEDerp1 3,6,7,14,16 without reaching statistical significance. However, since the sIgE production describes a non-linear curve and the commonly used method is an ELISA whose curve is not linear either, we can only say that there is a higher sIgE production for HDM group 2.…”
Section: Discussioncontrasting
confidence: 64%
“…However, as a whole, for the diagnosis of sensitization to HDM, IgEDerp1 and IgEDerp2 are sufficient as the most relevant allergens and capable of diagnosing >95% of patients 3,13 . Our series shows the presence of the phenotypes in production for IgEDerp1 and IgEDerp2 3,6,7,14,16 . The majority group DP (IgEDerp1 and IgEDerp2 double positives), significantly higher, followed by DN (double negative to IgEDerp1 and IgEDerp2) being the second most relevant group.…”
Section: Discussionmentioning
confidence: 70%
“…Of the currently known molecular components of HDMs, group 1 and 2 allergens (Der p 1, Der f 1, Der f 2 and Der f 2) as well as Der p 23 are considered to be the major sensitization elicitors on the American and the European continents [1,11]. However, scientists also include Dermatophagoides pteronyssinus Der p 5, Der p 7, Der p 21 allergens in the group of most clinically relevant ones [12,13].…”
Section: Introductionmentioning
confidence: 99%